The cultural turn in Community Interpreting. A brief analysis of epistemological developments in Community Interpreting literature in the light of paradigm changes in the humanities - Rudvin, Mette (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This essay traces some of the major epistemological shifts in the humanities over the last century, in particular anthropology, which have informed and profoundly altered language- and literary disciplines in Western academia, especially those relating to the subjectivity of the observer (the anthropological ‘gaze ’), the complex interconnectedness of language and the surrounding socio-cultural network, the ephemeral nature of language itself, and the issue of textual authorship-ownership. This paper attempts to put into relief the interface of philosophical issues that arises as a result of these paradigmatic shifts with practical issues of professional ethics and role-definition in community interpreting. The paper also attempts to show that what emerged in translation studies as the ‘cultural turn ’ has already taken place in community interpreting (not necessarily across the board in other forms of interpreting) due both to influences from other related domains and to the specific cross-cultural nature of community interpreting itself.